Pengaruh Return On Assets (ROA), Return On Equity (ROE), dan Debt To Equity Ratio (DER) Terhadap Harga Saham Pada Saham LQ45 (Periode 2019-2022) - Putri Agustina; Santi Oktavianti; Teuku Muhammad Haqiqi; M. Shalahuddin (Universitas Sumatera Selatan, 2024)
The purpose of this study was conducted to determine the effect of Return On Assets (ROA),Return On Equity (ROE), and Debt to Equity Ratio (DER) on stock prices in LQ45 stocks. This study contained 28 companies in LQ45 stocks that were always on the Indonesia Stock Exchange (IDX) list in 2019-2022. Sampling in study using purposive sampling method, data analysis used in this study is panel data regression analysis. The results of this study indicate that Return On Assets (ROA) has positive and significant effect on stock prices, Return On Equity (ROE) has a positive and insignificant effect on stock prices, and Debt to Equity Ratio (DER) has a negative and significant effect on stock prices.